Matt Shepard is a friend of mine [videorecording (DVD)] (Virgil Films and Entertainment, 2015)
A powerful feature documentary about Matthew Shepard, the gay young man who was tortured and murdered in one of the most notorious hate crimes in U.S. history. Directed by Michele Josue, a close friend of Shepard's, the film revisits the shocking case with never-before-seen photos, rare video footage, and new revelations about Shepard's all-too-brief life.